2009
DOI: 10.1007/s00024-009-0476-3
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Toughness and Fracture Roughness Interrelationship in Thermally treated Westerly Granite

Abstract: This paper presents an experimental work aimed at assessing the correlation between fracture toughness (K IC ) and fracture roughness for a series of Westerly granite specimens thermally treated up to 850°C. Mode I fracture toughness as a function of thermal treatment is determined using Cracked Chevron Notched Brazilian Disc specimens. The degree of roughness of the resultant fracture surfaces is analyzed with the aid of a high accuracy, high precision stereo-topometric measurement system. Roughness and tough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(28 citation statements)
references
References 34 publications
3
25
0
Order By: Relevance
“…We observed both increases and decreases in K IC , SCI, UCS, and elastic properties in damaged, altered, and cemented fault zone material. Mean K IC in relatively unaltered granodiorite from the Box Canyons is similar to reported values of K IC from Westerly granite (1.74 MPa√m, Atkinson, ; 1.79 ± 0.02 MPa√m, Meredith & Atkinson, ; 1.43 ± 0.05 MPa√m, Nasseri et al, ). SCI is similar to reported values for Lac du Bonnet granodiorite (55.9, 58.5, Wilkins, ; 56, Lajtai & Bielus, ) and Westerly granite (35.9–39, Atkinson, ; 69, Swanson, ).…”
Section: Discussionsupporting
confidence: 85%
“…We observed both increases and decreases in K IC , SCI, UCS, and elastic properties in damaged, altered, and cemented fault zone material. Mean K IC in relatively unaltered granodiorite from the Box Canyons is similar to reported values of K IC from Westerly granite (1.74 MPa√m, Atkinson, ; 1.79 ± 0.02 MPa√m, Meredith & Atkinson, ; 1.43 ± 0.05 MPa√m, Nasseri et al, ). SCI is similar to reported values for Lac du Bonnet granodiorite (55.9, 58.5, Wilkins, ; 56, Lajtai & Bielus, ) and Westerly granite (35.9–39, Atkinson, ; 69, Swanson, ).…”
Section: Discussionsupporting
confidence: 85%
“…If this induced stress due to thermal treatment exceeds the tensile or the shear strength of rocks, either new cracks will develop along those boundaries, or existing cracks will migrate, resulting in irreversible structural damage (Somerton, 1992;Tian et al, 2012). The findings of this experiment are in accordance with the results of Nasseri et al (2009), who evaluated the fracture toughness of thermally treated Westerly granite up to a temperature range of 850°C and observed a decreasing trend in the fracture toughness from untreated specimen to specimens treated at 850°C. This is possibly due to a variation in the thermal coefficient of expansion of minerals such as quartz, feldspar and mica, as a result of grain-grain boundary opening and increased micro-crack density.…”
Section: Temperature Vs Fracture Toughnesssupporting
confidence: 91%
“…Assuming that thermal microcracking in Westerly Granite is isotropic and homogeneous (Nasseri, Tatone, et al, ; and also shown to be the case in La Peyratte granite by C. David et al, ), and ignoring thermal strain effects, the relative time shift in the arrival times of scattered waves may be equated to a change in the velocity of the rock. We expect the coda to contain surface waves and multiple‐reflected waves, which are both sensitive mostly to changes in v S (Grêt et al, ; Snieder, ).…”
Section: Discussionmentioning
confidence: 99%